Progress and Development of Carbazole Scaffold Based as Potential Anti- Alzheimer Agents Using MTDL Approach - Kumar, Nitin; Gupta, Pankaj; Bansal, Sahil (Letters in Drug Design & Discovery, 2022)
Alzheimer's is a neurodegenerative disease (NDs) found in old age people with associated most common symptom dementia. MTDLs (Multi-Target Direct Ligand strategy) is based on a combination of two or more bioactive pharmacophores into a single molecule and this phenomenon has received a great attention in the new era of modern drug discovery and emerging as a choice to treat this complex Alzheimer’s disease (AD). In last fifteen years, many research groups designed, and synthesized new carbazole integrated molecules linked with other bioactive pharmacophores like thiazoles, carvedilol, α- naphthylaminopropan-2-ol, tacrine, ferulic acid, piperazine, coumarin, chalcones, stilbene, benzyl piperidine, adamantane, quinoline, phthalocyanines, α-amino phosphonate, thiosemicarbazones, hydrazones, etc. derivatives using MTDLs approach to confront AD. The present review entails the scientific data on carbazole hybrids as potential Anti-Alzheimer activities from 2007 to 2021 that have shown potential anti-Alzheimer activities through multiple target pathways thereby promising hope for new drug development to confront AD.
Keywords: acetylcholinesterase (AChE)